Plasma CTRP-3 concentration in obese and newly diagnosed Type II diabetes mellitus patients: A cross-sectional study - Kalsoom, Rizwana; Saeed, Muhammad; Rehan Khan, Muhammad; Umar, Samia; Ahmad, Irshad (ADVANCES IN BASIC MEDICAL SCIENCES, 2023)
Abstract Background: Cartonectin is a new adipokine belonging to the C1q complement/TNF-related protein (CTRP) class that has anti-inflammatory, glucose-lowering, and cardio-protective characteristics. We wanted to look the circulation cartonectin levels in people with type 2 diabetic mellitus (T2DM) BMI, age, and other biochemical parameters matched control people. Method: This study was conducted according to cross-sectional design. Results: Overall, our findings revealed that the mean concentration of serum cartonectin in recently diagnosed diabetes patients was considerably lower than in control groups. However, when it came to gender, male patients (0.43 ± 0.87) had a greater serum cartonectin content than female patients (0.24± 0.53), while control participants (2.34 ± 1.66 and 2.45 ± 1.68, respectively) had the opposite results. In patient participants, the mean serum cartonectin concentration was strongly related to their age groups. In patients, serum cartonectin concentrations rise with age and are unaffected by standard therapies. Furthermore, overweight patients had the lowest cartonectin concentration (0.247 ± 0.50) compared to normal and obese BMI (0.30 ± 0.75 and 0.78 ±1.136). FBS levels in patients were significantly higher than in controls (p=0.001). Furthermore, there were no significant variations in age, BMI, cholesterol, TG, HDL, LDL1, and VHDL across the examined groups. In comparison, patients’ FBS, GTT1, GTT2, GTT3, and cartonectin characteristics showed a significant difference. Conclusion: When compared to controls, serum cartonectin levels were shown to be lower in T2DM patients. The sub-factor study revealed that sex, BMI, age, FBS, and GTT all have a substantial impact on this relationship. Cartonectin emerges as a promising potential diagnostic for the prognosis and early recognition of T2DM patients, based on our findings. Keywords: Diabetic patients, Myocardial infarction, Cartonectin, Fasting Blood Glucose, Glucose Tolerance Test